Utility of basic research in plant/crop physiology in relation to crop improvement : A review and a personal account - El-Sharkawy, Mabrouk A. (FapUNIFESP, 2006)
Agricultural research and development plays an essential role in a nation's economic development, providing for food security for an ever-increasing population. In developed countries, the gap between potential and actual yield is largely closed because of a combination of advanced technologies, high-yielding new varieties and the application of agrochemicals in highly mechanized production systems. In most of these countries, agricultural production exceeds national demand, resulting in excess products for export. In many of the developing countries, however, agricultural productivity is still far below what it should be because of multiple technical and socio-economic constraints. Food deficits are the norm in poor and middle-income countries, requiring expensive food imports. To partially alleviate this situation, agricultural research must be strengthened. As branches of basic sciences, plant and crop physiology have often been criticized for being non-effective in translating their findings into improving crop productivity, which would enhance agricultural progress. This paper addresses this issue by presenting an assessment of past achievements of physiological research and their impacts on crop improvement and food production. Shortcomings and limitations of isolated, non-relevant research are discussed, along with scientist views on how effective physiological research should be conducted and integrated within breeding-based multidisciplinary research teams. Examples of successful research in crop physiology and their contributions towards increasing crop productivity are given. All this points to the need for steadfast funding of basic research by public and private sectors of developed countries.